Pengaruh Pendidikan Kesehatan dengan Media Video Animasi terhadap Pengetahuan dan Sikap Siswa tentang Bullying - Kamal, Fitri Amelia; Estria, Suci Ratna; Etlidawati, Etlidawati; Riyaningrum, Wahyu (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2025)
Bullying remains a serious problem in elementary schools and has a negative impact on students’ psychological health as well as their social relationships. Low levels of knowledge and response toward this behavior contribute to its high incidence. This study targeted fifth- and sixth-grade students at MI Muhammadiyah Dukuhturi, Bumiayu, Brebes, because at this age social interactions become increasingly complex, heightening the risk of both perpetrating and experiencing bullying. Effective prevention requires engaging and easily understood education, one of which is health education delivered through animated video that conveys information interactively. This research employed a quantitative pre-experimental design with a one group pretest–posttest approach. The entire population of 40 students was included as the sample using a total sampling technique because the population size was relatively small and the researchers aimed to obtain a comprehensive picture without inaccuracy from selecting only part of the respondents. The research instrument consisted of a knowledge and attitude questionnaire, while the intervention was carried out by screening an educational animated video of approximately four minutes’ duration, presented once in a scheduled session during a single learning activity. Data analyzed with a paired t-test showed an increase in mean knowledge scores from 29.65 to 35.62 and in attitude scores from 57,97 to 89,05, both with p = 0,0001 (p 0,05). These findings confirm that health education using animated video is effective in improving students’ knowledge and fostering positive attitudes toward bullying, making it a suitable and interactive educational method for bullying prevention in elementary schools. In line with these findings, the purpose of this study was to determine the effect of health education using animated video media on students’ knowledge and attitudes about bullying at MI Muhammadiyah Dukuhturi, Bumiayu.